Analysis of Potentiality and Projection of Market Service Levy Revenue in Semarang Regency - Evi Fatmawati; Karsinah Karsinah (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2017)
Market service levy is a kind of public service levy that is potential enough because Semarang Regency manages the levies from 33 traditional markets every day. The objective of this research is to analyze the potentiality of market service levy revenue in Semarang Regency in 2011-2015 and to find out the projection of market service levy in 2016-2010. This research uses the analysis of contribution, the analysis of growth, the analysis of potentiality, and the analysis of ARIMA (2,1,2) (Auto Regressive Integrated Moving Average). The results of this research show as follows: (1) the contribution of market service levy to the regional levy and PAD (the own-source revenue) is in the insufficient and very insufficient category, (2) the growth of market service levy is fluctuating, (3) the market service levy revenue has not based on the potentiality yet, (4) the target of market service levy is under the potentiality, and (5) the projection of market levy revenue will increase in the next five years. The researcher suggested that the target setting should be based on the potentiality and the quality of market service should be improved, so that those may increase the contribution of market service levy to PAD.